Phymonotus glyphopyrenos sp. nov. (Orthoptera, Tettigoniidae, Nedubinae): a new California high elevation mountain endemic katydid with a built-in amplifier - Cole, Jeffrey A.; Bailey, James P.; Weissman, David B.; Warchałowska-Śliwa, Elżbieta (Zootaxa, 2026)
Using morphology, bioacoustics, cytogenetics, and molecular phylogenetics, we tested whether a disjunct Phymonotus population from the highest peak in San Diego County, California, is distinct from the only known species, the San Jacinto Mountains endemic P. jacintotopos Lightfoot, Weissman, and Ueshima, 2011. The results prompt the description of P. glyphopyrenos sp. nov., a new extremophilic species with adult activity at high elevations during cold winter conditions. Morphologically, male genitalia and color pattern are generally diagnostic. Acoustically, P. glyphopyrenos have song energy spread out over a wider bandwidth than do P. jacintotopos (dominant frequency range 3.48±1.19 vs. 1.07±0.58 kHz; time entropy 0.88±0.11 vs. 0.70±0.09). The 2n♂=22 (20t+Xt+Yt) karyotype is distinct from 2n♂=24 (22t+Xt+Yt) described from P. jacintotopos. Bayesian consensus trees of the ITS2 barcode gene, both alone and concatenated with six other genes, clustered the two species into separate monophyletic lineages. We resurrect the subfamily Nedubinae for the monophyletic basal katydid lineage that includes Aglaothorax, Neduba, and Phymonotus. We contrast the habitats of both Phymonotus species, update the distribution of Phymonotus using community science observations, and hypothesize about the evolution of the peculiar dome-shaped male pronotum.